(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
The Human Genome Project began in 1990 with the task of mapping the genes that would compose the human genetic code. Recently, the general coordinator of the Cancer Genome Project in Brazil, suggested the existence of a set of genes responsible for criminal behavior, discarding the relevant role of environmental variables (ontogenetic and cultural). The present essay aims to discuss the origin and pertinence of the biologic reductionist determinism in the explanation of behavior. It was identified a long tradition in the occidental thought to search, in the organic basis, for a strictly biological explanation for human actions, specially for those considered socially problematic. Such tradition is confronted to Skinner’s model of selection by consequences and to the description of experiments showing the collective action of the phylogenetic and ontogenetic determinants in behavior. The limits of an entirely genetic explanation of action and the social and political risks of its dissemination are discussed.